Effect of Problem-Based Learning Model on Biology Learning Motivation and Conceptual Understanding - Muliana, Haika; Ramdani, Agus; Kusmiyati, Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Education plays a crucial role in shaping high-quality human resources. However, observations at SMA Negeri 5 Mataram revealed that students are less motivated to participate in classroom learning. This is evident from students' lack of attention to the teacher’s explanation and their difficulty in understanding the material. One of the main causes is the use of monotonous, teacher-centered learning methods. This condition calls for innovation in teaching, such as implementing the Problem-Based Learning (PBL) model, which is designed to improve students’ motivation and conceptual understanding. This study aims to analyze the effect of the problem-based learning model on students’ learning motivation and understanding of biological concepts among Grade X students at SMA Negeri 5 Mataram. The research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group, involving an experimental group and a control group with both pretest and posttest. The sample was selected using purposive sampling, with class X6 as the control group and class X7 as the experimental group. The instruments used were a questionnaire to measure learning motivation and an essay test to assess conceptual understanding. The data were analyzed using the Mann-Whitney test, which showed a significant difference between the experimental and control groups, with a significance value of 0.000 < 0.05. These findings indicate that the problem-based learning model has a positive effect on improving both learning motivation and conceptual understanding. A good understanding of concepts can enhance students’ confidence in learning, thereby increasing intrinsic motivation. With strong motivation and conceptual understanding, students tend to achieve better academic outcomes and are more prepared to continue learning and adapting to future challenges.